THE MARITAL STATUS AND THE HAPPINESS - Navaitis, Gediminas; Labutis, Gintaras; Kairienė, Brigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The changes in the family as the social institution that are described as the second demographic transition revealed the reality of new social links, affected the selection of the strategies and methods of family establishment and led to the family de-institutionalization processes. The changes had also affected the status of formal and informal roles in the family. Those changes catalyzed the greater variety of families and households which can be illustrated by the spread of cohabitation and the increased numbers of children born outside the traditional marriage. The above changes demonstrate the conscious choices to family relationship building. Present research paper aims to find out how does the human happiness which is mostly described by a subjective well-being index depend on the family status.